A computational study of a new design configuration for a turbulence tunnel. (29th July 2021) - Anoop, M V; Panchapakesan, N R
Abstract: A new kind of turbulence tunnel, the pure coherent shear source turbulence tunnel, proposed to produce high Reynolds number, approximately homogeneous isotropic turbulence is studied computationally. The Reynolds-averaged Navier–Stokes equations, along with the standard k − ϵ model for closure, are solved in the computations. The tunnel design studied here consists of a duct of square cross section with a plane at one end consisting of an array of round jets and suction vents. This plane, referred to as the momentum source plane (MSP), also a zero net-mass flux plane, forces the flow into the tunnel. The flow field inside consists of an advection-dominated region where the jets merge to form a combined flow, and an advection-free near-homogeneous turbulence region. Turbulence statistics in the advection-dominated and advection-free regions of the flow field, and the effect of parameters associated with the forcing that affects these statistics are studied. A plateau of turbulence statistics with rms of fluctuations as high as 0.8 times the mean advective velocity scale for the tunnel section, U T, is obtained in a region with negligible mean advection. The effect of geometrical configuration at the MSP on the turbulence quantities in the advection free region is studied. The Reynolds number based on Taylor length scale R λ of the turbulence produced is estimated to be of the order of 350 in a tunnel of size 0.5 × 0.5 m 2 .